2015
DOI: 10.1007/s10452-015-9509-4
|View full text |Cite
|
Sign up to set email alerts
|

Local environment overrides regional climate influence on regime shift in a north temperate lake

Abstract: Regime shifts in shallow lakes are typically characterized by submerged macrophyte (clear water regime) or phytoplankton (turbid regime) dominance. Climate warming is expected to affect water quality and facilitate turbidity in lakes, but we may also expect synergistic effects on organisms' interactions from climate and local specific dynamics in lakes. We here examined long-term changes in phytoplankton composition in July and August from 1980 to 2011 in a temperate shallow lake, Lake Krankesjön, a dataset in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…In early summer, phagotrophic nutrient acquisition might have helped in becoming the dominant phytoplankton community member, but Cryptomonas reached its highest absolute abundances during the most eutrophic conditions in fall. Both the high total phosphorus concentrations during this time and the occurrence of cyanobacterial blooms are in line with earlier reports from Lake Krankesj€ on (Hargeby et al 2007;Zhang et al 2015) and represent a temporal pattern more frequently observed in shallow lakes (Søndergaard et al 2002), but are not typically considered favorable conditions for mixotrophs. Nevertheless, Cryptomonas also showed relatively higher importance in more eutrophic lakes in South America (Saad et al 2016) indicating that nutrient limitation is not necessarily the major driver for phagotrophy in this species.…”
Section: Environmental Drivers and Seasonal Dynamicssupporting
confidence: 91%
“…In early summer, phagotrophic nutrient acquisition might have helped in becoming the dominant phytoplankton community member, but Cryptomonas reached its highest absolute abundances during the most eutrophic conditions in fall. Both the high total phosphorus concentrations during this time and the occurrence of cyanobacterial blooms are in line with earlier reports from Lake Krankesj€ on (Hargeby et al 2007;Zhang et al 2015) and represent a temporal pattern more frequently observed in shallow lakes (Søndergaard et al 2002), but are not typically considered favorable conditions for mixotrophs. Nevertheless, Cryptomonas also showed relatively higher importance in more eutrophic lakes in South America (Saad et al 2016) indicating that nutrient limitation is not necessarily the major driver for phagotrophy in this species.…”
Section: Environmental Drivers and Seasonal Dynamicssupporting
confidence: 91%
“…In terms of alternative temperature effect, warmer surface waters may actually stimulate herbivory (Berger et al 2010;Boersma et al 2016), suggesting strengthening top-down control of phytoplankton biomass by zooplankton. In Swedish lakes, phytoplankton biomass was more strongly controlled by grazing rates and nutrient availability than by any direct temperature effect (Zhang, Xu, and Hansson 2015). Further, zooplankton grazing suppresses phytoplankton biomass near surface waters but may promote increased autotrophic biomass in deeper mixed layers (Pannard, Planas, and Beisner 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Typically, cyanobacteria thrive in warmer, more nutrient-rich lakes with shallow mixing depths (Hamilton, Salmaso, and Paerl 2016). Nevertheless, studies have also noted that cyanobacteria may dominate in more nutrient-poor systems with high levels of zooplankton grazing (Zhang, Xu, and Hansson 2015) or in warmer, deeper mixed layers under lightlimiting conditions (Kovacs, Presing, and Voros 2016). Significant increases in the biomass of chlorophytes, dinoflagellates, diatoms, chrysophytes, and cryptophytes occurred due to experimental deepening of the mixed layer in a Canadian lake (Cantin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature was thus a significant environmental factor affecting the diversity, community structure and function of bacterioplankton, and it might be also a factor that promoted regime shifts of bacterioplankton community in water bodies. There may be an early warning temperature that serves as an indicator for steady state transformation ( Zhang et al, 2015 ; Anderson et al, 2018 ; Rosero-López et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%